Does physical activity lower the risk for metabolic syndrome: a longitudinal study of physically active older women - Zając-Gawlak, Izabela; Pelclová, Jana; Groffik, Dorota; Přidalová, Miroslava; Nawrat-Szołtysik, Agnieszka; Kroemeke, Aleksandra; Gába, Aleš; Sadowska-Krępa, Ewa (BMC geriatrics, 2021)
BACKGROUND: The associations between physical activity and metabolic syndrome (MetS) have been mainly found in cross-sectional studies. The aim of this longitudinal study was to examine the relationship between meeting step-based guidelines and changes in the risk of metabolic syndrome. METHODS: This study included data from older women (baseline age 62.9 ± 4.3 years) from a 7-year longitudinal study in Central Europe. At baseline and follow-up, physical activity was measured by an accelerometer, and the risk for MetS was assessed according to the NCEP-ATP III criteria. In 59 women, multivariate repeated measures ANOVA was used to compare differences in changes in the risk of MetS in groups based on meeting step-based guidelines (10,000 steps/day and 9000 steps/day for women aged <65 and ≥ 65 years, respectively). RESULTS: Over 7 years, steps/day increased from 10,944 ± 3560 to 11,652 ± 4865, and the risk of MetS decreased from 41 to 12% in our sample. Women who longitudinally met step-based guidelines had a significantly higher mean concentration of high-density cholesterol (HDL-C) (64.5 and 80.3 mg/dL at baseline and follow-up, respectively) and a lower concentration of triglycerides (TGs) (158.3 and 123.8 mg/dL at baseline and follow-up, respectively) at follow-up compared to baseline. Moreover, women who increased their daily steps over 7 years to the recommended steps/day value significantly decreased the concentration of TGs (158.3 mg/dL and 123.8 mg/dL at baseline and follow-up, respectively). CONCLUSIONS: Our study might suggest that the long-term meeting of step-based guidelines or an increase in daily steps/day to achieve the recommended value could be related to a lower risk of MetS, specifically in concentrations of HDL-C and TG. These findings may help in designing interventions aiming to decrease the risk of MetS in older women.
Keywords: Cross-Sectional Studies; Daily physical activity; longitudinální studie; Risk Factors; Number of steps; Europe; Aged; senioři; metabolický syndrom; Exercise; MetS components; Metabolic Syndrome; Evropa; lidé; ženské pohlaví; Humans; Accelerometer; rizikové faktory; průřezové studie; Longitudinal Studies; Female; cvičení; Health